Evaluasi Kinerja Badan Permusyawaratan Desa dalam Penyelenggaraan Pemerintahan Desa - Alamsyah Hamonangan Simbolon; Walid Mustafa Sembiring (Universitas Medan Area, 2015)
This research is to discuss (1) how the existence (presence) of Section Peace and Order in supporting local government programs in District Lubukpakam Deli Serdang, (2) What efforts are made Sexy Peace and Order in carrying out their duties and functions, (3) the obstacles and constraints encountered any Section of Peace and Order as well as the ways to overcome them. The method used is a qualitative description as a method of data analysis which took place at the Head Office study Lubukpakam Peace and Order Section. Sources of data in this study is the Peace and Order Section Head Lubukpakam. Data were collected by interviews and documentation by using the steps of editing, classification and presentation of data. The results of this study showed that the duties and functions of Peace and Order Section plays an important role in helping the main tasks of Head and Regional Head (Bupati) in establishing and running a local government program in the field of peace and public order in the district level. One way is to conduct a routine patrol of morning, afternoon, into the evening alternately. Efforts were made and the obstacles encountered and how to overcome divided into several areas: the institutional field, the field of networking, counseling field, field operations, field of action, and ends with anticipation field routine.